2023
DOI: 10.1029/2023jd038565
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Measurement and Molecular Compositions of Atmospheric Water‐Soluble Brown Carbon in the Nearshore Marine Boundary Layer of Northern China: Secondary Formation and Influencing Factors

Abstract: Understanding the evolution of brown carbon (BrC) in the atmosphere is essential for investigating its climate effects. This study deployed a novel in‐situ BrC continuous observation system to firstly measure water‐soluble BrC absorption (AbsWS‐BrC) in an offshore island over the Bohai Sea in the winter of 2020. The AbsWS‐BrC abundance before the cold wave (BCW) was more than twice higher than that after the cold wave (ACW). This was mainly ascribed to the substantially suppressed formation of secondary WS‐BrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 154 publications
(291 reference statements)
1
5
0
Order By: Relevance
“…88 Li et al built upon this observation by showing that increased brown carbon SOA correlated with increases in RH, aerosol water content, and nitrogen precursors (e.g., NO 2 , NO 3 − , and NH x ). 89 Further in line with this narrative are observations from Li et al, who noted an increase in organonitrates (specifically nitrophenols and nitrocatechols) with increased RH and aerosol water content. 90 It is therefore possible that for the captured ambient conditions on April 17, the unique aloft MF (notably the dominance of CHNO compounds) may be related to aqueous phase processing.…”
Section: Case Study Analysis Of April 17supporting
confidence: 55%
See 1 more Smart Citation
“…88 Li et al built upon this observation by showing that increased brown carbon SOA correlated with increases in RH, aerosol water content, and nitrogen precursors (e.g., NO 2 , NO 3 − , and NH x ). 89 Further in line with this narrative are observations from Li et al, who noted an increase in organonitrates (specifically nitrophenols and nitrocatechols) with increased RH and aerosol water content. 90 It is therefore possible that for the captured ambient conditions on April 17, the unique aloft MF (notably the dominance of CHNO compounds) may be related to aqueous phase processing.…”
Section: Case Study Analysis Of April 17supporting
confidence: 55%
“…Cheng et al showed that high RH enhanced the formation of brown carbon SOA (often related to biomass burning) in spite of low temperatures . Li et al built upon this observation by showing that increased brown carbon SOA correlated with increases in RH, aerosol water content, and nitrogen precursors (e.g., NO 2 , NO 3 – , and NH x ) . Further in line with this narrative are observations from Li et al, who noted an increase in organonitrates (specifically nitrophenols and nitrocatechols) with increased RH and aerosol water content .…”
Section: Resultsmentioning
confidence: 87%
“…This suggests a significant secondary formation of BrC. This Abs BrC,L-HULIS,sec (365) magnitude was lower than that of secondary WS-BrC before the cold wave (5.42 ± 4.84 Mm 1 ), but during the summer campaign comparable to that observed after the cold wave (1.27 ± 0.99 Mm 1 ) (Li, Qin, et al, 2023). During the winter campaign, Abs BrC, L-HULIS,sec (365) was higher in Chengdu, Lanzhou, and Wuhan, but it was the lowest in Shanghai during the summer campaign.…”
Section: Examination Of Secondary Source Of Brc Determined By L-hulismentioning
confidence: 63%
“…This suggests that, besides this secondary source, other sources may also contribute to WS-BrC in this winter campaign. Li, Qin, et al (2023) assessed the contribution of secondary WS-BrC using the MRS method on Juehua Island before and after a cold wave. Before the cold wave, secondary WS-BrC was found to contribute 60% of WS-BrC at 365 nm, which decreased to 33% after the cold wave.…”
Section: Examination Of Secondary Source Of Brc Determined By L-hulismentioning
confidence: 99%
See 1 more Smart Citation